Torque excêntrico do quadril, joelho e tornozelo em indivíduos com e sem tendinopatia patelar - Ferreira, Ana Luisa Granado (2015)
Background: Patellar tendinopathy (PT) is an overuse injury, but the factors that contribute to tendon overload are still unknown. The high prevalence of this injury in jumping athletes may be related to hip extensor and ankle plantar flexor weakness, which could lead to a preferential use of the quadriceps to absorb the impact forces acting on the lower limbs during landing. However, no previous study has evaluated hip and ankle strength in subjects with PT. Therefore, the aim of this study was to evaluate the eccentric hip and knee extensor and ankle plantar flexor peak torques and the knee/hip and knee/ankle ratios in athletes with symptomatic PT (SPTG), athletes with asymptomatic patellar tendon ultrasonographic abnormalities (APTG) and healthy controls (CG). Methods: Seventeen athletes (volleyball, basketball and handball) between 16 and 35 years of were enrolled in this study. They were divided into three groups: SPTG (n=6), APTG (n=5) and CG (n=6). Eccentric peak torque was evaluated with an isokinetic dynamometer. Differences between groups were evaluated by multivariance analysis (MANOVA) and the Tukey post-hoc test (α=0.05). Results: The SPTG had a lower eccentric knee extensor torque than the APTG (p=0.047) and the CG (p=0.035), and the APTG had a higher knee/ankle ratio than the SPTG (p=0.015). Conclusions: The SPTG had lower knee extensor torque than the other groups, which may have been due to pain inhibition. Additionally, the APTG had a higher knee/ankle ratio than the other groups, which may have been related to increased patellar tendon load. Prospective studies are needed to investigate whether these aspects are risk factors for PT.